2022
DOI: 10.3390/nu14030596
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet Is Associated with Better Metabolic Features in Youths with Type 1 Diabetes

Abstract: Our aim was to evaluate adherence to the Mediterranean diet (MedDiet) among children and adolescents with type 1 diabetes (T1D) in relation to metabolic control. Adherence to the MedDiet was assessed with the Mediterranean Diet Quality Index (KIDMED)questionnaire and physical activity by the International Physical Activity Questionnaire for Adolescent (IPAQ-A) on 65 subjects (32 males, 9–18 years) with T1D. Clinical and metabolic evaluation was performed (standardized body mass index(BMI-SDS), hemoglobin A1C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 78 publications
(88 reference statements)
6
17
0
Order By: Relevance
“…KIDMED scores displayed average values in 58.6% of the subjects, in line with data from a non-diabetic population of Italians of the same age range [8]. Low adherence to the MD was associated with a high risk of obesity in T1D, as reported in the general pediatric and adult population [17]. Regarding the prospective relation between diet pattern and total cancer risk, Yiannakou et al [18] examined in a prospective study the longitudinal association between the Mediterraneanstyle dietary pattern (MSDP) score, derived from a semi-quantitative food frequency questionnaire, and total cancer risk in 2966 participants of the Framingham Offspring Study cohort, displaying weaker association between MSDP score and cancer risk in men except in non-smokers, while higher adherence to MSDP was associated with lower cancer risk, especially among women [18], confirming that the MD as a source of bioactive compounds protects against cancer [19].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…KIDMED scores displayed average values in 58.6% of the subjects, in line with data from a non-diabetic population of Italians of the same age range [8]. Low adherence to the MD was associated with a high risk of obesity in T1D, as reported in the general pediatric and adult population [17]. Regarding the prospective relation between diet pattern and total cancer risk, Yiannakou et al [18] examined in a prospective study the longitudinal association between the Mediterraneanstyle dietary pattern (MSDP) score, derived from a semi-quantitative food frequency questionnaire, and total cancer risk in 2966 participants of the Framingham Offspring Study cohort, displaying weaker association between MSDP score and cancer risk in men except in non-smokers, while higher adherence to MSDP was associated with lower cancer risk, especially among women [18], confirming that the MD as a source of bioactive compounds protects against cancer [19].…”
supporting
confidence: 85%
“…Apart from the studies evaluating adherence to the MD in different contexts, also interesting was the relationship between diet and some metabolic and chronic diseases, such as type 1 diabetes (T1D) and cancer. In this scenario, Antoniotti et al [17] assessed the MD adherence by the Mediterranean Diet Quality Index (KIDMED) questionnaire in 65 children and adolescents with T1D in relation to metabolic control. KIDMED scores displayed average values in 58.6% of the subjects, in line with data from a non-diabetic population of Italians of the same age range [8].…”
mentioning
confidence: 99%
“…Two cross‐sectional studies 14,15 also found an association between adherence to the Mediterranean diet and better glycaemic control in children and adolescents with T1D. Another study conducted in youth with T1D 16 showed the benefit of a number of dietary habits typical of the Mediterranean diet (consumption of dairy products at breakfast, extra virgin olive oil or fish) with lower HbA1c and blood pressure.…”
Section: Discussionmentioning
confidence: 96%
“…In primary and secondary prevention RCTs, increased adherence to the Mediterranean dietary pattern has been shown to significantly reduce major cardiovascular events 11–13 . In people with T1D, greater adherence to the Mediterranean diet has been associated with improved glycaemic control 14,15 and various metabolic parameters 16 . However, little information is available on the relationship of the Mediterranean diet with atherosclerosis and CVD 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Persons on medications to lower blood cholesterol should monitor their cholesterol levels. Various cautions are indicated [49] . Skin: Fruit and leaves are used in leprosy.…”
Section: Isolation Of Charantinmentioning
confidence: 99%